Differentiating AC and DC Field Effects on the Magnetic Susceptibility of Bulk YBa_2Cu_3O_(7-d) - Afalla, Jessica Pauline C.; Sarmago, Ronald V. (Science Diliman: A Journal of Pure and Applied Sciences, 2010)
A low field AC magnetic susceptibility has been measured for a superconducting bulk YBa 2 Cu 3 O 7- d sample with an AC excitation field superimposed with a DC field. The effects on the susceptibility due to either type of field have been interpreted without any assumption regarding the presence of vortices in the material. From the in-phase susceptibility data, saturation values show that increasing the AC field strength causes a decrease in shielding ability and a persistence of intergranular losses to lower temperatures. The intergranular loss peaks in the out of phase susceptibility data show shifting to lower temperature in accordance with the in-phase data. Increasing the DC field strength does not cause the saturation values to decrease, but rather, saturation values remain at the same level for the in-phase susceptibility data, showing consistency in the sample’s shielding ability. However, increasing DC field strength increases the peak height for the intergranular loss peaks, but the peak does not shift to lower temperatures, thus greater energy is expended to shield the DC excitation, but without causing losses to persist to lower temperatures.
Keywords: Magnetic properties; Transition temperature variations; Y-based cuprates